Responsibilities of Business Actors to Consumers Due to Incompatibility of Objects and Specifications in Electronic Transaction Agreements - Rahmat Bijak Setiawan Sapii; Ersa Hamzah (Catuspata, 2022)
This article aims to determine the legal protection for the violation or non-fulfilment of consumer rights in transactions conducted electronically and to determine the form of responsibility of online business actors for acts of default against consumers in transactions conducted electronically. Then, this research is normative juridical research supported by a statutory approach. In addition, this research is also supported by various data sources, including primary legal materials in the form of laws and regulations, secondary legal materials consisting of books and scientific journals, and tertiary legal materials covering various complementary information and data originating from various websites on the Internet. The results of the study explain that in conducting transactions of goods and/or services, especially those carried out electronically, various laws and regulations such as UUPK, UU ITE, and PP concerning the Implementation of Electronic Systems and Transactions have guaranteed the rights of consumers and provided obligations to business actors. In this case, if the consumer's rights are violated or, in other words, the business actor does not carry out his obligations. The consumer is entitled to compensation or compensation. Therefore, as a form of responsibility for the occurrence of violations of consumer rights in the form of receiving goods or objects and specifications that do not match the specifications, business actors are obliged to provide compensation. If this cannot be fulfilled, it is possible to take various litigation and non-litigation dispute resolution options.